Internet censorship detected in Ethiopia (Ethiopia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Ethiopia. Data sourced from CensoredPlanet.
Censorship Incident ID: ET-2026-0033. Severity: critical. Confidence: 65%